A new, prairie-restricted species of Filatima Busck (Lepidoptera: Gelechiidae) from Illinois - Harrison, Terry L.; Berenbaum, May R. (Zootaxa, 2013)
Filatima revisensis (Gelechiidae) is described from individuals collected as larvae feeding inside shelters constructed of silked-together leaflets of leadplant, Amorpha canescens (Fabaceae). Filatima revisensis is bivoltine; overwintering occurs in the larval stage. Because this insect is restricted to tallgrass prairie, it is likely to be of concern to conservation biologists. In the interest of naming this moth and clarifying its identity, a description is provided, and diagnoses are given to differentiate it from F. ornatifimbriella, F. xanthuris, F. adamsi, and F. occidua, all of which are externally similar to F. revisensis.